2000
DOI: 10.1590/s0041-87812000000500004
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophic calcinosis in a child with a thumb sucking habit: case report

Abstract: We present an uncommon case of a 3-year-old boy with a finger sucking habit who developed dystrophic calcification in his left thumb. Two years after excision, there was no recurrence, and the thumb retained full range of motion. We also discuss its probable pathogenesis and present a brief review of the literature about orthopedic complications in the hand due to this habit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Various forms of trauma have also been implicated in dystrophic calcification. There have been reported cases of calcium deposition secondary to burn wounds, repeated trauma, needle sticks in the heels of neonates, thumb sucking by children, radiation and surgery (2-4). Although rarely seen in the genitourinary tract, it has been associated with schistosomiasis (5), renal and ureteral tumors (6), renal parenchymal disease (7), Churg-Strauss vasculitis (8), and polyarteritis nodosa (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various forms of trauma have also been implicated in dystrophic calcification. There have been reported cases of calcium deposition secondary to burn wounds, repeated trauma, needle sticks in the heels of neonates, thumb sucking by children, radiation and surgery (2-4). Although rarely seen in the genitourinary tract, it has been associated with schistosomiasis (5), renal and ureteral tumors (6), renal parenchymal disease (7), Churg-Strauss vasculitis (8), and polyarteritis nodosa (9).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue injury promotes calcification in two ways. Damaged cell membranes leak calcium ions into cells, and these ions are subsequently concentrated by mitochondria to levels that are high enough to form crystals (2, 4). It has also been suggested that necrosis creates an acidic environment that lacks calcification inhibitors (12).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of calcium deposition secondary to burns, repeated trauma, neonatal heel sticks, thumb sucking in children, radiation, and surgery have been reported (6,11,24). If calcifications are limited in size and location, they are referred to as calcinosis circumscripta.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue injury promotes calcification in two ways. Damaged cell membranes leak calcium ions into cells, which are subsequently concentrated by mitochondria to levels high enough for crystal formation (6,24). It has also been suggested that necrosis creates an acidic environment that lacks calcification inhibitors (23).…”
Section: Discussionmentioning
confidence: 99%
“…Hemangiomas made up about 13% of hand tumours in people aged 0 to 15 in research on benign tumours reported by previous study in 1994. Hemangiomas are the fourth most common hand vascular tumour, according to Figueiredo et al, (2000) on vascular tumours in the upper limbs. A common endothelium tumour in children and infants is the hemangioma.…”
Section: Introductionmentioning
confidence: 99%